SYMBOLISM OF NINE GREAT HOUSES IN GAME OF THRONES - Putri, Dwi Wira Wasistha (LITERA : Jurnal Bahasa Dan Sastra, 2024)
This study entitled â€œSymbolism of Nine Great Houses in Game of Thronesâ€. It aims at identifying symbols that are applied and analyzing the meanings of the symbols implied in each house based on the semiosis process proposed by Peirce. All the data are taken from the Nine Great Houses by watching it repeatedly and listing all the symbols that are related to each house. The writer will identify the symbols that are found and analyses them by using qualitative descriptive methods continued with the semiosis process. The writer chose the Theory of Symbol proposed by Charles Sanders Peirce to analyze the symbols by using his triadic structure which included Object, Representamen, and Interpretant. All three parts must be present for something to be considered a sign or symbol. The results show that four type of Archetypal Symbols found, they are Symbolism of Animals, Symbolism of Colors, Symbolism of Settings, and Symbolism of Objects. These differences have resulted in various interpretations.